Ответы и объяснения

  • Участник Знаний
2013-06-22T14:16:49+04:00

((k-3)(k+3))^2  - (2+k)

 

 при k= 2.5

 

((2,5-3)(2,5+3))² - (2+2,5) = 7,5625 -4,5 = 3,0625

 

 

  • AlbuRin
  • светило науки
2013-06-22T14:18:31+04:00

!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

 

((k-3)(k+3))^2 - (2+k)   при к=2,5

 

((2,5-3)(2,5+3))^2 - (2+2,5) =   (-0.5*5.5)^2  -  4.5 =

=(-2.75)^2 - 4.5 = 7.5525 - 4.5 = 3.0525